The mechanism of domain-wall structure formation in Ar-Kr submonolayer films on graphite - Patrykiejew, A.; Soko\lowski, S. (Condensed Matter Physics, 2014)
Using Monte Carlo simulation method in the canonical ensemble, we have studied the commensurate-incommensurate transition in two-dimensional finite mixed clusters of Ar and Kr adsorbed on graphite basal plane at low temperatures. It has been demonstrated that the transition occurs when the argon concentration exceeds the value needed to cover the peripheries of the cluster. The incommensurate phase exhibits a similar domain-wall structure as observed in pure krypton films at the densities exceeding the density of a perfect (√3x√3)R30º commensurate phase, but the size of commensurate domains does not change much with the cluster size. When the argon concentration increases, the composition of domain walls changes while the commensurate domains are made of pure krypton. We have constructed a simple one-dimensional Frenkel-Kontorova-like model that yields the results being in a good qualitative agreement with the Monte Carlo results obtained for two-dimensional systems. Використовуючи метод моделювання Монте-Карло в канонiчному ансамблi, ми дослiдили перехiд вiд
спiввимiрної до неспiввимiрної фази у двовимiрних скiнчених змiшаних кластерах Ar i Kr, адсорбованих
на графiтнiй базиснiй площинi при низьких температурах. Показано, що перехiд вiдбувається, коли концентрацiя аргону перевищує значення, необхiднi для покриття периферiй кластера. Неспiввимiрна фаза
демонструє подiбну структуру доменної стiнки до тої, яка була спостережена у плiвках чистого криптону при густинах, що перевищують iдеальну (
p
3 ×
p
3)R30◦
спiввимiрну фазу, але розмiр спiввимiрних
доменiв значно не змiнюється зi змiною розмiру кластера. Коли концентрацiя аргону зростає, склад доменних стiнок змiнюється, в той час як спiввимiрнi домени складаються з чистого криптону. Ми побудували просту одновимiрну модель Френкеля-Конторової, яка приводить до результатiв, що добре якiсно
узгоджуються з результатами Монте-Карло, отриманими для двовимiрних систем.